2007
DOI: 10.1007/s10801-007-0096-x
|View full text |Cite
|
Sign up to set email alerts
|

On the independence complex of square grids

Abstract: The enumeration of independent sets of regular graphs is of interest in statistical mechanics, as it corresponds to the solution of hard-particle models. In 2004, it was conjectured by Fendley et al., that for some rectangular grids, with toric boundary conditions, the alternating number of independent sets is extremely simple. More precisely, under a coprimality condition on the sides of the rectangle, the number of independent sets of even and odd cardinality always differ by 1. In physics terms, this means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 8 publications
0
83
0
Order By: Relevance
“…Their method relies on the assumption that one of the generators of I is of the form (±m, ±m); as of today, it remains unclear whether it is possible to extend their method to arbitrary groups I . Bousquet-Mélou, Linusson, and Nevo [1] examined the homology of other square grids with free and cylindrical boundary conditions. Fendley and Schoutens [5] computed the (co-)homology of the independence complex of octagon-square and enneagon-triangle grids; see Sect.…”
Section: Related Workmentioning
confidence: 99%
“…Their method relies on the assumption that one of the generators of I is of the form (±m, ±m); as of today, it remains unclear whether it is possible to extend their method to arbitrary groups I . Bousquet-Mélou, Linusson, and Nevo [1] examined the homology of other square grids with free and cylindrical boundary conditions. Fendley and Schoutens [5] computed the (co-)homology of the independence complex of octagon-square and enneagon-triangle grids; see Sect.…”
Section: Related Workmentioning
confidence: 99%
“…This case is discussed by Bousquet-Mélou et al in [3], who calculate P N (x) for N = 1,... , 10. We have extended these calculations to N = 1,... , 12 and give the Table 2.…”
Section: Free and Fixed Boundary Conditionsmentioning
confidence: 97%
“…More recently, Jonsson ([9]) has investigated the effect of first rotating the lattice through 45 • before imposing toroidal boundary conditions, and Bousquet-Mélou et al ( [3]) have looked at the problem using free boundary conditions. Again they found that P N (x) is a product of simple factors.…”
Section: Introductionmentioning
confidence: 99%
“…The application motivating this method is in the study of the independence and dominance complexes of a graph, which have been extensively studied in the recent years [6,11,12,[18][19][20][21]27] because of their applications in graph theory, network analysis, and statistical mechanics. Our method allows us to obtain several results on the topology of the independence and dominance complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In Sect. 6 we apply the method of the core to the dominance complex Δ of a forest F . We prove that Δ always collapses onto the boundary of a cross-polytope whose dimension equals the matching number of F .…”
Section: Introductionmentioning
confidence: 99%